Pendampingan Pembelajaran Bahasa Inggris Berbasis MOOC di Sekolah Terbuka Madani Depok - Indrayani, Septina; Sukaesih, Ina; Hasyim, Nur; Kurniawati, Dewi; Humolungo, Farizka; Sari Safitry, Tantri (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
Madani Open School Depok is an alternative educational institution serving junior and senior high school students who are unable to attend regular schooling. This school faces various challenges, such as limited access to technology, low student motivation, minimal learner engagement, and a lack of teaching materials that support effective learning, particularly in English subjects. To address these issues, this community service activity aims to develop and assist in the implementation of a Learning Management System (LMS) based on Massive Open Online Courses (MOOC) to improve the quality of English language learning. The method used is Service Learning (SL), which involves the direct application of academic knowledge by lecturers and students in the community. The activity consists of five main stages: MOOC socialization, instructional content design, training and mentoring in LMS use, monitoring of student learning progress, and the development of an integrated evaluation system. The results of the activity indicate that an LMS based on MOOC provides an effective solution for improving access, quality, and participation in learning. Additionally, the school now has a digital learning system that supports attendance tracking, assignment submission, and the provision of learning materials that can be accessed flexibly by students.  Keywords—LMS, MOOC, English Language Learning, Open School Abstrak Sekolah Terbuka Madani Depok merupakan lembaga pendidikan alternatif yang melayani siswa SMP dan SMA yang tidak dapat bersekolah di jalur reguler. Sekolah ini menghadapi berbagai tantangan, seperti keterbatasan akses teknologi, rendahnya motivasi belajar siswa, minimnya keterlibatan peserta didik, dan kurangnya materi ajar yang mendukung pembelajaran efektif, khususnya dalam mata pelajaran Bahasa Inggris. Untuk menjawab permasalahan tersebut, kegiatan pengabdian ini bertujuan mengembangkan dan mendampingi penerapan Learning Management System (LMS) berbasis Massive Open Online Courses (MOOC) guna meningkatkan kualitas pembelajaran Bahasa Inggris. Metode yang digunakan adalah Service Learning (SL), yang melibatkan penerapan keilmuan oleh dosen dan mahasiswa secara langsung di tengah masyarakat. Kegiatan terdiri dari lima tahapan utama: sosialisasi MOOC, perancangan konten ajar, pelatihan dan pendampingan penggunaan LMS, pemantauan progres belajar siswa, serta penyusunan sistem evaluasi terintegrasi. Hasil kegiatan menunjukkan bahwa LMS berbasis MOOC memberikan solusi efektif dalam meningkatkan akses, kualitas, dan partisipasi pembelajaran. Selain itu, sekolah kini memiliki sistem pembelajaran digital yang mendukung absensi, pengumpulan tugas, serta penyediaan materi ajar yang dapat diakses secara fleksibel oleh siswa.Kata kunci—LMS, MOOC, Pembelajaran Bahasa Inggris, Sekolah Terbuka